Addressing multimodality in culturally responsive pedagogy: A case study of Indonesian primary EFL classrooms - Idaryani; Lynde Tan (Studies in English Language and Education, 2026)
This paper aims to examine a range of semiotic modes used in Culturally Responsive Pedagogy (CRP) by two English language teachers in teaching young EFL learners in Lhokseumawe, Aceh, Indonesia. It evaluated the contributing factors in applying the diverse modes, drew the implications, and proposed practical solutions for effectively integrating CRP within an Indonesian primary school setting. Data were gathered through classroom observations and semi-structured interviews. The observations focused on one fifth-grade and one sixth-grade classroom, supplemented by approximately four hours of audio-recorded classroom observations. The findings revealed the dominant inhibiting factors in incorporating multimodal literacy into the presentation of CRP. The significant issue was a lack of teachers’ skills and knowledge to adopt various modes that engage with young learners. The use of multimodal texts, such as images and gestures, remained limited, with a predominant reliance on traditional text-based methods and endorsed textbooks. Furthermore, the teachers struggled to connect CRP with students’ real-life experiences, which is essential for promoting engagement and understanding. Consequently, when teachers failed to leverage the unique characteristics of young students, the learning environment was often tedious and stressful for both teachers and learners. The study emphasizes the need for targeted professional development to enhance teachers’ knowledge and skills in multimodal literacies, facilitating more effective CRP delivery to young learners. The implications and practical solutions to these challenges are thoroughly discussed, highlighting the significance of adapting teaching practices by teachers to meet the needs of young EFL learners.